Identification of functional lncRNAs based on competing endogenous RNA network in osteoblast differentiation. Issue 3 (4th September 2019) - Hong, Shuai; Hu, Supei; Kang, Zhengyang; Liu, Zhiguo; Yang, Weibin; Zhang, Yongzhi; Yang, Dengfeng; Ruan, Wenhui; Yu, Guoyong; Sun, Liang; Chen, Liang
Abstract: Adult human mesenchymal stem cells have the potential to differentiate into osteoblast, which plays crucial roles in bone regeneration and repair. Some transcriptional factors (TFs), such as BMP‐2 and RUNX2, have been demonstrated to control the differentiation processes. It is important to discover more key regulators in osteoblast differentiation. Recently, some studies found long noncoding RNAs (lncRNAs) participating in osteoblast differentiation, such as MALAT1, DANCR, and ANCR. In this study, we performed a network‐based computational analysis to investigate the lncRNA–messenger RNA (mRNA) crosstalks via integrating microRNA (miRNA)–RNA interactions, gene coexpression, and protein–protein interactions. First, multiple topology analyses were performed to osteoblast‐differentiation‐related lncRNA–mRNA network (ODLMN). Several lncRNAs with central topology structures were identified as key regulators. Results showed that these lncRNAs participated in osteoblast differentiation via phosphoinositide 3‐kinase (PI3K), mitogen‐activated protein kinase, and Ras signals. Previous studies have demonstrated that lncRNAs exert functions by involving in close modules. Second, after performing module searching in ODLMN, two functional modules were identified, which played crucial roles through involving in PI3K/protein kinase B, cyclic adenosine 3ʹ, 5ʹ‐monophosphate, and hypoxia‐inducible factor 1 pathways. Third, a subset of core lncRNA–TF crosstalks that might form feedback loops to control the biological processes in osteoblast differentiation was identified. These core lncRNA–TF feedback loops showed more TF binding affinity than other lncRNAs. All these results can help us to uncover the molecular mechanism and provide new targets for bone regeneration and repair. Abstract : We constructed the osteoblast‐differentiation‐related competing endogenous RNA network and identified the functional long noncoding RNAs (lncRNAs) in the differentiation processes. We found that core lncRNA–messenger RNA (mRNA) feedback loops play crucial roles in the osteoblast differentiation.